Fatal pulmonary complication during induction therapy in a patient with ANCA-associated vasculitis - Jonaitytė, Brigita; Kibarskytė, Rūta; Danila, Edvardas; Miglinas, Marius; Šeinin, Dmitrij; Stulpinas, Rokas; Mitrikevičienė, Jurgita; Gruslys, Vygantas; Šileikienė, Virginija; Zablockis, Rolandas (Acta medica Lituanica, 2016)
ANCA-associated vasculitis (AAV) is an inflammatory systemic disorder affecting small to medium sized vessels and likely leading to any organ dysfunction. Adequate treatment is important to avoid mortality or severe organ damage. In most cases initial treatment (induction therapy) allows to achieve remission. Induction therapy leads to immunosuppression and may cause severe infections. However, in vasculitis patients even an intensive immunosuppressive therapy is rarely complicated by an invasive fungal infection. We present a case in a 29-year old male patient with newly diagnosed AAV. He suffered a fatal pulmonary complication of the induction immunosuppressive treatment. Pathological (infectious) changes in the lungs were misinterpreted as progression of the vasculitis and he died due to disseminated angioinvasive aspergillosis. A clinical course, imaging and histopathology of this case are described and discussed.